2004
DOI: 10.1093/occmed/kqh108
|View full text |Cite
|
Sign up to set email alerts
|

The diagnostic value of finger systolic blood pressure and cold-provocation testing for the vascular component of hand-arm vibration syndrome in health surveillance

Abstract: There is little evidence that the described form of finger rewarming after cold-provocation testing is a useful diagnostic test for vascular HAVS, although it may have some moderate influence in ruling out vascular problems. Based on our data, the FSBP may also have limited use in confirming a positive diagnosis of vibration-induced vascular problems. The higher specificity of the FSBP test suggests it may have some value in ruling out the vascular component of HAVS. The data from this study do not confirm the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…The most commonly applied methods in the assessment of abnormal vascular response to cold in HAVS are the measurements of finger skin temperature and finger systolic blood pressure after subjecting fingers or hands to cold exposure. It has been reported that the skin temperature rewarming test may lack the necessary sensitivity and specificity for distinguishing between regular vascular reactivity and cold-induced vasospasm [28][29][30] . The diagnostic value of the finger systolic pressure test can be difficult to define, as there has been a variation in both the nature of the cooling procedure and the outcome parameter used [31][32][33] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most commonly applied methods in the assessment of abnormal vascular response to cold in HAVS are the measurements of finger skin temperature and finger systolic blood pressure after subjecting fingers or hands to cold exposure. It has been reported that the skin temperature rewarming test may lack the necessary sensitivity and specificity for distinguishing between regular vascular reactivity and cold-induced vasospasm [28][29][30] . The diagnostic value of the finger systolic pressure test can be difficult to define, as there has been a variation in both the nature of the cooling procedure and the outcome parameter used [31][32][33] .…”
Section: Discussionmentioning
confidence: 99%
“…This result suggests that the method may offer information on both aspects of the vascular reflection to cold, namely, the vasoconstrictive response to cold exposure and that following vasodilatation. In this regards, a number of researchers have reported that the finger systolic pressure test constantly shows high specificity but somewhat lower sensitivity 29,35,38) . Among the blood perfusion variables determined in this study, the false-positive cases appeared to be fewer when the value of the immersion phase was used rather than the other variables.…”
Section: Discussionmentioning
confidence: 99%
“…Poole et al reported a comparatively low sensitivity and high specificity: the sensitivity was between 44 and 61%, and the specificity was between 91 and 95% 51) . On the other hand, Thompson et al reported a comparatively high sensitivity (94%) and low specificity (15%) 54) .…”
Section: Strain Gauge Plethysmography (Arterial Occlusion)mentioning
confidence: 99%
“…In the investigation undertaken by Suizu and Harada, the ISO 14835-1 test method with measurement of FST by thermistors was found repeatable 20) . The reported sensitivity and specificity from several studies involving thermometry 10,[21][22][23][24][25][26][27][28][29] and thermography [29][30][31] with a cold water immersion test in distinguishing VWF patients from controls are presented in Table 2, which indicates that the diagnostic ability of FST measurements with cold provocation is inconsistent. In the study of Coughlin et al, the researchers investigated the potential of cold provocation thermography with a water temperature of 5°C for 1 min as an objective test to diagnose the digital vasospasm in HAVS patients 31) .…”
Section: Thermometry and Thermographymentioning
confidence: 99%
See 1 more Smart Citation